SARS-CoV-2 screening strategies for returning international travellers: Evaluation of a rapid antigen test approach. (May 2022) - Layer, Emily; Hoehl, Sebastian; Widera, Marek; Bojkova, Denisa; Westphal, Tim; Gottschalk, Rene; Boeddinghaus, Boris; Schork, Joscha; Ciesek, Sandra; Goetsch, Udo
Highlights: International travel enables the spread of SARS-CoV-2 and its viral variants The antigen test showed a sensitivity of 100% with respect to in vitro infectivity An antigen test following quarantine effectively detects infectious travellers Travel regulations rely heavily on test quality and compliance Abstract: Background: International travel poses the risk of importing SARS-CoV-2 infections and introducing new viral variants into the country of destination. Established measures include mandatory quarantine with the opportunity to abbreviate it with a negative rapid antigen test (RAT). Methods: A total of 1, 488 returnees were tested for SARS-CoV-2 with both PCR and RAT no earlier than 5 days after arrival. We assessed the sensitivity and specificity of the RAT. Positive samples were evaluated for infectivity in vitro in a cell culture outgrowth assay. We tracked if participants who tested negative were reported positive within 2 weeks of the initial test. Results: Potential infectiousness was determined based on symptom onset analysis, resulting in a sensitivity of the antigen test of 89% in terms of infectivity. The specificity was 100%. All positive outgrowth assays were preceded by a positive RAT, indicating that all participants with proven in vitro infectivity were correctly identified. None of the negative participants tested positive during the follow-up. Conclusions: RAT no earlier than the 5th day after arrival was a reliable method for detecting infectious travellers and can be recommended as an appropriate method for managing SARS-CoV-2 travel restrictions. Compliance to the regulations and a high standard of test quality must be ensured.